The Effect of Staff Accountability on the Quality of E-Procurement Services at the Logistics Bureau - Tati Julita; Yuni Candra; Yudas Sabaggalet (CV Edujavare Publishing, 2026)
This study aims to examine the effect of staff accountability on the quality of e-procurement services at the Logistics Bureau. Accountability is regarded as a fundamental principle of good governance that ensures transparency, responsibility, and efficiency in the implementation of public procurement services. This research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to employees and service users. The collected data were analyzed using descriptive and inferential statistical techniques, including simple linear regression, to determine the relationship between staff accountability and service quality. The findings indicate that staff accountability has a positive and significant effect on the quality of e-procurement services. Employees who demonstrate higher levels of responsibility, transparency, and compliance with procurement regulations contribute to faster, more accurate, and more reliable service delivery. These results suggest that strengthening staff accountability through continuous training, effective supervision, and performance evaluation can improve the overall quality of e-procurement services. The study concludes that accountability is a key determinant in enhancing public service performance and recommends that government institutions reinforce accountability practices to achieve more effective, efficient, and transparent procurement processes.